The Impacts of Crowding Restaurant Image and Consumer Satisfaction on The Intention to Revisit - Ningrum, Priskilah Febi Widya; Wahyuningtyas, Agustina Shinta Hartati; Andriani, Dwi Retno (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 18 No 2 (2024): Vol 18 No 2 (2024), 2024)
Human and spatial crowding presents a significant challenge in the restaurant industry, particularly influencing the likelihood of customers returning. This study aimed to examine the impact of human and spatial density on the perception of a restaurant's image and the satisfaction of its patrons, as well as to assess how these perceptions influence customers' intentions to revisit. The research involved 100 participants, who were surveyed using an online questionnaire distributed through Google Forms. Data analysis was conducted utilizing the Structural Equation Modeling approach with WarpPLS 8.0 software. The findings revealed that both human and spatial crowding positively affect the restaurant's image and customer satisfaction. In turn, a positive image of the restaurant and high levels of customer satisfaction were found to significantly influence patrons' intentions to return to the spicy noodle restaurant. These insights suggest that restaurants could strategically leverage the presence of crowding to enhance their image and elevate customer satisfaction, thereby supporting business sustainability and encouraging repeat visits